PERAN KOMNAS PERLINDUNGAN ANAK INDONESIA DALAM PENCEGAHAN DAN PENANGANAN KASUS KEKERASAN PADA ANAK - Indah Aryani; Irfan Haris; Sheila Zulfiani; Miladia Shiva; Asya Ilfana; Laila Fikriyani; Karomatul Khusna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Violence against children is a serious social problem that continues to increase in Indonesia, with profound impacts on children's development. The Indonesian National Commission for Child Protection (Komnas PA) exists as an independent institution that plays a crucial role in preventing and handling cases of violence against children. This article aims to examine the role of Komnas PA in two main dimensions: preventing violence through education, outreach, public campaigns, and policy advocacy; and handling cases through complaint services, victim assistance, counseling, and legal advocacy. This study uses a descriptive qualitative approach with library research and field observations at the Komnas PA Jakarta Office. Data were collected through field observations, activity documentation, and a review of official documents and child protection regulations. The results indicate that Komnas PA has played a strategic role in building a holistic child protection system. However, several challenges remain, including budget constraints, low public awareness in reporting cases, and suboptimal cross-sectoral coordination. Strengthening institutional capacity, synergy between stakeholders, and the integration of child protection education into the early childhood education curriculum are the main recommendations resulting from this study.